Use of 3d printing in physical study in higher education institutions - Токарев, П. Л. (Scientific notes of the pedagogical department, 2017)
The article is devoted to the consideration of one of the pressing issues of modern applied physics – additive technologies. A comparative review of domestic studies on the theory of 3D printing technology and the practical possibility of their use in education has been made. The article theoretically substantiates the use of a 3D printer and discusses the possibilities of using 3D printing  technologies in teaching physics in high school. The key points of additive technologies are revealed: the physical meaning of 3D printing, the scope of application, development prospects, and the advantages and disadvantages of additive technologies; the insufficient investigation of this problem in theoretical science and didactics of physics has been established. The physical meaning of the  3D printing process is considered: the construction of an object is based on layers that are sequentially plotted; and materials (thermoplastics) that can be used to create a 3D object using a 3D printer. The advantages of 3D printing compared with the creation of an object manually are highlighted: high speed of execution, affordable material cost, ease of creation of an object. The possibilities of using software for creating 3D-objects on the example of the common Cura slicer program (modes of operation and interface) are considered. A step-by-step process of creating a digital version of a future 3D object is considered: from creating a file in the STL format and converting it into G-code to the moment it is loaded into a 3D printer. An introduction to the course of high school physics for the study of additive technologies with the aim of attracting students to engineering, design and invention was proposed.  Examples of tasks that can be solved in the course of high school physics using computer simulation and 3D printing are given. The article reveals the theoretical and practical aspects of the introduction of additive technologies in the course of physics of higher education, proposals for further research.